Ultrasonic-assisted galvanic displacement synthesis of Pt–Pd/MWCNT for enhanced oxygen reduction reaction: Effect of Pt concentration. (13th April 2017) - Zapata-Fernández, J.R.; Gochi-Ponce, Y.; Salazar-Gastélum, M.I.; Reynoso-Soto, E.A.; Paraguay-Delgado, F.; Lin, S.W.; Félix-Navarro, R.M.
Abstract: The most important issue for proton exchange membrane fuel cells (PEMFC) is the catalyst which is predominantly Pt-based materials. The simple and fast galvanic displacement (GD) method is a novel alternative does not require any surfactants, additive reagent, or post-treatment in the synthesis of bimetallic materials. The parameters investigated were Pt concentration and sonication in GD bath, finding that both play a key role in the physicochemical features, and thereby, modifying the performance of the catalysts towards the oxygen reduction reaction (ORR) activity. The materials obtained by GD were studied using TGA, ICP-OES, TEM and evaluated as catalysts for ORR in acidic media. Among all synthesized catalysts, highly dispersed Pt10 Pd90 /MWCNT synthesized by GD in sonication, exhibited the highest electrocatalytic activity and H2 O2 was not detected, showing as a promising catalyst for the use in PEMFC applications. Graphical abstract: Highlights: The effects of sonication and Pt concentration on the synthesis were investigated. GD reaction was performed under sonication, without addition of additives or treatment. Narrowed size distribution and well dispersed bimetallic NPs are synthesized by GD. The catalytic activity of different Pt–Pd/MWCNT was evaluated for ORR by RDE and RRDE. The best catalyst showed the lowest transfer charge resistance and H2 O2 was not detected.